KAJIAN TERHADAP PERAN PEJABAT PEMBUAT AKTA TANAH MENURUT PERATURAN PEMERINTAH NOMOR 24 TAHUN 1997 TENTANG PENDAFTARAN TANAH - Asri Agustiwi, S.H., M.H,; Bintara Sura Priambada, S.Sos., M.H (RECHTSTAAT, 2014)
The land owners to which some right inherent and each use of such the right obligatorily has the evidence of right-to land ownership called land deed; to obtain such the deed, some registration should be passed through for the land owned to which some right inherent, in order to prevent some problems from occurring in the future. The objective of research was to study and to find out the role of Land Deed Making Official (PPAT) according to Government Regulation Number 24 of 2007 about Land Registration the writer took from Notary and PPAT Office owned by IMMAWATI USWATUN CHASANAH, S.H., M.Kn. This study was expected to improve and to develop the learning material and teaching book in legal science, particularly in Faculty of Law of Surakarta University, and to give input and knowledge increase for those related who wanted to register their rights through Land Deed Making Official (PPAT), in addition to find out how the mechanism of right-to-land registration is. This study was a normative sociological research. Technique of collecting data used were structured interview, observation, supported by library study and the data collected was analyzed qualitatively. The Notary and PPAT office in the right-to-land registration served as an official institution appointed by the stated as the government’s arm in disciplining the publication of right-to-land owned by individual or enterprise, by authenticating the right in the form of deed. In this case, the applicants who wanted their right legally usually appointed Notary and PPAT to propose whether right transfer, exhortation (wasiat) or trade on an object of right-to-land to be registered in National Land Affairs Agency (BPN). The Notary and PPAT office later would deal with any completeness and prerequisite including the cost spent by the applicant until the publication of deed for what the applicants had applied. Meanwhile, the constraints the notary and PPAT office of Immawati encountered in the process of registering the applicants’ right was not too severe, because it was technical constraint only in the right application process; the constraint from the applicant usually included less complete data, particularly regarding the beneficiaries; the constraints from the National Land Affairs Agency included the less number of BPN personnel leading to the delayed document checking in the application process to right registration.